2019
DOI: 10.3920/bm2018.0028
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic or synbiotic alters the gut microbiota and metabolism in a randomised controlled trial of weight management in overweight adults

Abstract: The gut microbiota contributes to host energy metabolism, and altered gut microbiota has been associated with obesity-related metabolic disorders. We previously reported that a probiotic alone or together with a prebiotic controls body fat mass in healthy overweight or obese individuals in a randomised, double-blind, placebo controlled clinical study (ClinicalTrials.gov NCT01978691). We now aimed to investigate whether changes in the gut microbiota may be associated with the observed clinical benefits. Faecal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
103
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(110 citation statements)
references
References 46 publications
4
103
1
2
Order By: Relevance
“…in the human fecal microbiota, while the prevalence of Paraprevotella spp. was reduced [40]. Christensenellaceae positively correlated with the fecal branched chain fatty acids (BCFAs) [40], which in previous studies have been indicated to inhibit de novo lipogenesis, thus potentially affecting lipid and glucose metabolism in human adipocytes [41].…”
Section: Gut Microbiota Composition In Obesitymentioning
confidence: 95%
See 2 more Smart Citations
“…in the human fecal microbiota, while the prevalence of Paraprevotella spp. was reduced [40]. Christensenellaceae positively correlated with the fecal branched chain fatty acids (BCFAs) [40], which in previous studies have been indicated to inhibit de novo lipogenesis, thus potentially affecting lipid and glucose metabolism in human adipocytes [41].…”
Section: Gut Microbiota Composition In Obesitymentioning
confidence: 95%
“…As a consequence of the above-mentioned ability of microbes to affect energy metabolism, the most important step in the mode of action of probiotics in metabolic health outcomes might well be inducing a beneficial shift in microbiota composition. The effect of B420 on microbiota composition was studied as part of a placebo-controlled human intervention trial [40]. The results indicated that B420 consumption modulated the gut microbiota-both alone, as well as in synbiotic product containing prebiotic fiber with probiotic-of an overweight study population towards the composition associated with a lean phenotype [40].…”
Section: Gut Microbiota Composition In Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Porphyromonadaceae was positively correlated with body weight [24]. At the family level,Streptococcaceae was enriched in the NAFLD group [25,26].…”
Section: Discussionmentioning
confidence: 93%
“…Hibbert et al reported a study involving both probiotic and prebiotic interventions in a randomized, double-blind, placebo-controlled trial of 134 overweight adults [24]. This study included four treatment groups (1) placebo (microcrystalline cellulose) (2) treatment with the prebiotic Litesse Ultra ® polydextrose (LU), (3) Bifidobacterium animalis subsp.…”
Section: Overweight/obesitymentioning
confidence: 99%